Integrating formal surveys and local knowledge: Insights into the subterranean fauna of Apulia - Sarah Boulamail; Salvatore Inguscio; Sara Ventruti; Benedetta Barzaghi; Damiano Brognoli; Raffaele De Giorgi; Joachim Langeneck; Elia Lo Parrino; Emanuele Mancini; Raoul Manenti; Alejandro Martínez; Martina Pulieri; et al. (Subterranean Biology)
The study of hypogean fauna is critical for preserving subterranean biodiversity and ecosystem functions despite climate change. However, underground habitats, often hosting unique and endemic species, present significant challenges for traditional biodiversity assessments owing to their inaccessibility and the specialised nature of their inhabitants, resulting in a paucity of academic studies. Furthermore, even when these studies exist, data are often held in personal notes and databases that are not interoperable according to current standards, making them less usable for research purposes. Reawakening this dormant data, standardising, and sharing it according to modern criteria offers enormous opportunities to expand existing knowledge and provide support for future studies. In the Apulian region of Southern Italy, a biodiversity hotspot for subterranean life, the paucity of recent systematic surveys and reliance on expert knowledge poses both opportunities and challenges for ecological research. By integrating data from various sources, this study provides an overview of the subterranean faunal assemblages documented in this region. Overall, the dataset is comprehensive, comprising 109 species (29 of which are considered endemic to Apulia) and 224 sites, totalling 622 presence-only records. As our records have expanded over 93 years, this dataset represents a unique resource for elucidating the characteristics of Apulian subterranean ecosystems and potentially their changes over time. Integrating observations already published in previous studies with unpublished records, this is the first complete data collection on Apulian subterranean fauna organised according to modern standards of data sharing.